Autograft choice and jumping performance after anterior cruciate ligament reconstruction - a comparative study on professional athletes - Torre, G.; Vasta, S.; Rocchi, J.; Papalia, R.; Paolo Mariani, P. (Orthopaedic Journal of Sports Medicine, 2024)
Background: The extensor apparatus of the knee is of paramount importance in generating the torque needed for a countermovement jump (CMJ), especially in jumping athletes. In anterior cruciate ligament reconstruction (ACLR) procedures, graft harvesting from the extensor apparatus may dramatically affect extensor strength and jumping performance.